advise,aviser (Le Grand Robert & Collins, 2024)
The essential bilingual French-English dictionary With Le Grand Robert & Collins, discover every translation of a word or a phrase. Its powerful search engine instantly finds the appropriate translation in context. It’s the expert’s tool for reliable and accurate translations.